Monitoring of arthropod bioindicators in urban areas: objectives, experiences, and perspectives - Sanchez Jardon, Laura; Ramos Miranda, Beatriz; Gomez Peral, Emma; Bunster, Claudia; Acosta-Gallo, Belen (My University, 2022)
The sub-Antarctic ecoregion of Chile, which includes the administrative regions of Aysen and Magallanes, is characterized by its high degree of endemicity and the uniqueness of its species given its proximity to Antarctica. In particular, the sub-Antarctic channels and fjords, with more than 100 000 km of coastline and a complex geomorphology, is one of the largest estuarine zones in the world and harbors a high diversity of marine mammals that is in any case higher than the values recorded in more temperate areas of southern South America. However, biodiversity data records in this southern zone are still scarce and, when they do exist, they are published exclusively in specialized journals inaccessible to local communities. This lack of information hinders the design of conservation strategies on a regional scale and local socioeconomic development, such as the development of tourism specialized in whale watching or experiences similar to other regions of the southern cone. In this context and in order to visualize and integrate the existing records of marine mammals in information repositories, an exhaustive review of this group of organisms is proposed. A total of 484 records or sightings of marine mammals present in the Aysen region between 1852 and 2016 were compiled from bibliography published in specialized journals, books and technical documents. A total of 28 species, 6 belonging to the Order Carnivora (Families Mustelidae, Otariidae and Phocidae) and 22 to the Order Cetacea (Families Balaenidae, Balaenopteridae, Delphinidae, Hyperoodontidae, Phocoenidae and Physeteridae). This data collection began with the Biodiversity Information System for Aysen (SIB-Aysen) and continued with the Open Laboratory for Sub-Antarctic Sciences. Eventually it will be complemented with the observations of citizens associated with the SIB-Aysen. The relevance of integrating biodiversity datasets into open repositories as an essential tool for designing conservation policies and promoting, as far as possible, economic development initiatives based on knowledge of their natural heritage is discussed.
Keywords: biodiversity databases; chilean patagonia; gbif; sub-antarctic region; whale watching